Biology of red-banded mango caterpillar, its infestation to different mango cultivars and control (Bangladesh Journal of Agricultural Research, 2007)
Three intensive mango growing areas of Chapai Nawabgonj District, namely Sadar, Shibgonj, and Gomostapur were selected to determine the pest status of red-banded mango caterpillar (Noorda albizonalis, Hampson). Results indicated the highest levels of 9.92, 9.59, and 7.64% fruit infestation to Aswina, Gopalbhog, and Gooti varieties, respectively, at Gomostapur followed by 6.19, 5.81, and 5.03% fruit infestations in Gooti, Aswina, and Gopalbhog, respectively at Shibgonj. Mango varieties at Chapai Nawabgonj Sadar showed low levels of fruit infestation ranging from 0.96 to 3.26% Considering all those locations together, Aswina and Gopalbhog variety showed higher levels of fruit infestation of 8.50 and 6.21%, respectively, whereas Amrapali, Mohananda, Langra, and Fazli showed lower levels of fruit infestations ranging from 1.51 to 3.77%. Full-grown caterpillars are 17.6 0.38 mm long, red-banded in colour, and slightly hairy, and they pupate inside the infested fruits. The pupal length is 12.8 0.28 mm. The larval, pupal, and the adult longevity periods are 19.5 0.56, 11.25 0.54, and 6.0 0.35 days, respectively. The adult moths measured 13.25 0.54 mm in length when the wings are expanded. Moths are fawn coloured with scaly wings and a prominent white band present dorsally at the joint of the thorax and the abdomen. Female moths lay their eggs on he peduncle of the mango fruits and after 7 to 8 days hatch into larvae. Considering the pest status of the RBMC, 16 treatments with insecticides were applied twice as a full cover spray on mango trees. Based on the percent reduction (more than 80%) of fruit infestation over untreated control, Emithion, Sumithion, Lebaycid, Shobicron, Mipcin, and Sevin were the best among the tested insecticides for the effective control of RBMC. The spraying with other insecticides including botanical neembicidin produced 61-75% reduction of fruit infestation and might be the next choice for the control of red-banded mango caterpillar. Bangladesh J. Agril. Res. 32(2) 2007: 215-223.